2020
DOI: 10.1111/codi.14925
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and functional outcomes following pelvic exenteration and sacrectomy

Abstract: AimThe aim was to compare postoperative quality of life (QOL) between patients undergoing pelvic exenteration (PE) and pelvic exenteration with sacrectomy (PES), and to investigate the influence of high (L5-S2) vs low (≤ S3) sacrectomy on QOL and functional outcomes.Method Patients undergoing en bloc sacrectomy as part of a PE and PE alone from 2008 to 2015 were identified from a prospectively maintained database. ResultsOf the 344 patients identified, data were available for 116 patients who underwent PE alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…In APR with flap reconstruction, complications, such as wound dehiscence, flap failure and perineal hernia, may have higher incidence when en bloc sacrectomy is additionally undertaken, with a higher transection level on the sacrum associated with higher perineal complication rates [ 38 , 39 , 40 ]. In fact, higher transections may be associated with higher all-cause morbidity, including physical function, pain, quality of life and bladder function [ 1 , 2 , 3 , 4 ], although other studies dispute this [ 13 , 18 , 41 ].…”
Section: Postoperative Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In APR with flap reconstruction, complications, such as wound dehiscence, flap failure and perineal hernia, may have higher incidence when en bloc sacrectomy is additionally undertaken, with a higher transection level on the sacrum associated with higher perineal complication rates [ 38 , 39 , 40 ]. In fact, higher transections may be associated with higher all-cause morbidity, including physical function, pain, quality of life and bladder function [ 1 , 2 , 3 , 4 ], although other studies dispute this [ 13 , 18 , 41 ].…”
Section: Postoperative Complicationsmentioning
confidence: 99%
“…To achieve this where tumours invade or are adherent to the sacrum, en bloc sacrectomy at a radiologically predetermined level is the current standard of care. Sacral resection remains technically challenging, and the morbidity rises sequentially with higher levels of transection [ 1 , 2 , 3 , 4 ]. Major uncontrolled haemorrhage is a feared complication of sacrectomy, with 80% of patients shedding over a litre of blood and requiring at least one haemostatic agent [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who undergo pelvic exenteration with sacrectomy are usually known to have worse outcomes than pelvic exenteration alone due to the involvement of sacral nerves, affecting lower limb, urinary and bowel function, sexual health and overall quality of life [6,21,22]. High en bloc sacrectomy is associated with worse functional and quality of life outcomes in comparison with low en bloc sacrectomy [22,23]. However, most studies that examine postoperative outcomes of pelvic exenteration are focused on survival, postoperative complications, recurrence rates and patient-reported outcomes, and studies that objectively assess physical function are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The paper by McCarthy et al [4] in this issue is one of the first to use patient reported outcome measures following pelvic exenteration, with and without high or low sacrectomy. While there are inevitable limitations, this study is from a group with a strong track record in this field and describes highly relevant quality of life and functional outcomes in what is large and mature cohort given the rarity of this surgery.…”
mentioning
confidence: 99%